2020
DOI: 10.26452/ijrps.v11i1.1951
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Red Blood Cell Distribution Width (RDW) and Hemoglobin A1C (HbA1c) Levels, In Patients with Type 2 Diabetes Mellitus

Abstract: The incidence of Diabetes Mellitus is increasing worldwide, with almost 1/3 of adults being affected. It is the major contributor to the morbidity of a man with its multi-organ system complications. Control of blood glucose levels is vital to decrease organ damage and complications. Routine diagnostic tests conducted are blood glucose, lipid pro ile, renal function tests, HbA1c, and insulin assays with a baseline CBC (Complete Blood Count). HbA1c values continue to be the gold standard for the assessment of gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
2
1
Order By: Relevance
“…This is consistent with the previous studies conducted in Pakistan 35 and India. 36 However, our finding is contrary to another study conducted in India reported that no significant correlation ( r =0.04, p>0.05) between RDW and HbA1c levels in T2 DM patients. 37 The difference might be due to the small number (only 50 T2 DM) of patients involved in the previous study.…”
Section: Discussioncontrasting
confidence: 99%
“…This is consistent with the previous studies conducted in Pakistan 35 and India. 36 However, our finding is contrary to another study conducted in India reported that no significant correlation ( r =0.04, p>0.05) between RDW and HbA1c levels in T2 DM patients. 37 The difference might be due to the small number (only 50 T2 DM) of patients involved in the previous study.…”
Section: Discussioncontrasting
confidence: 99%
“…Many studies have shown an association between the RBC indices and HbA1C. [8][9][10][11][12][13][14][15][16][17] From the red blood cell (RBC) indices, mean corpuscular volume (MCV) indicates the size of RBCs, while mean corpuscular hemoglobin (MCH), and mean corpuscular hemoglobin concentration (MCHC) define the hemoglobin content of RBCs. The red cell distribution width (RDW), however, indicates the variation in size of RBCs.…”
Section: Introductionmentioning
confidence: 99%
“…A study in Chennai, India with a sample of 610 Type 2 DM patients reported a significant relationship between RDW and HbA1c (OR= 1.36; p= 0.003) (Biswas and Srinivasan, 2020).…”
mentioning
confidence: 97%